Design of a universal antenna-based problem simulation interface with emphasis on geometric data capturing and handling - Rokebrand, Timothy M (My University, 2020)
The design of a simulation framework that allows for interaction with multiple computational engines through a single interface is presented. The framework was designed, not only to combine these engines under a single interface but also to simplify the design process, this was achieved by making use of macro-based design. These macros are used to build antenna arrays by automatically defining the dimensions of base elements that make up the array using the simulation frequency as reference. For more advanced users, there is the option to make use of scripting, which allows for more optimisation driven design to take place. The framework takes the user inputs from either the graphical or scripting interfaces and, using the macros, creates input files formatted to pass into the simulation engines. The engine then performs the calculations and produces an output file that is then used to provide requested outputs. An implementation of the framework that is able to run simulations in both NEC++ and FEKO is provided. Testing entailed running simulations with dipole, Yagi-Uda and rectangular patch geometries. The results showed that the program was able to successfully capture data from the user, convert these user inputs into simulation files that could then be executed to complete simulations effectively. Results from the different computational engines were similar and these aligned with literature. This is evidence that the framework is successful in its objective of providing a universal simulation platform using multiple engines, while the geometric information is captured once
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Engineering, 2020